Quantum Sensing and Nanophotonic Devices XII 2015
DOI: 10.1117/12.2080195
|View full text |Cite
|
Sign up to set email alerts
|

Uni-travelling carrier photodetectors as THz detectors and emitters

Abstract: The THz part of the spectrum (0.1 to 10 THz) has been gathering increasing interest over the past 10 years as it could enable interesting new applications. Key to its exploitation has been the development of photonic based sources and detectors. However there is a lack of room temperature operating devices for both sources and detectors. We propose the use of uni-travelling carrier photodetectors (UTC-PDs) as both source and detectors for the range up to 2 THz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although these photodetectors are mature and capable of achieving the high bandwidth required for mm-wave communications, their power handling capability may be limited. For higher power operation that may obviate the need for amplifiers, and for scalability to even higher (potentially terahertz) frequencies, unitraveling-carrier photodiodes (UTC-PDs) are particularly attractive [24]. These photodiodes provide sufficient power to directly drive integrated antennas and can be hybrid integrated with low-loss waveguides based on SiPh or PLC technology.…”
Section: Millimeter-wave Photonic Communications and Arraysmentioning
confidence: 98%
“…Although these photodetectors are mature and capable of achieving the high bandwidth required for mm-wave communications, their power handling capability may be limited. For higher power operation that may obviate the need for amplifiers, and for scalability to even higher (potentially terahertz) frequencies, unitraveling-carrier photodiodes (UTC-PDs) are particularly attractive [24]. These photodiodes provide sufficient power to directly drive integrated antennas and can be hybrid integrated with low-loss waveguides based on SiPh or PLC technology.…”
Section: Millimeter-wave Photonic Communications and Arraysmentioning
confidence: 98%
“…Superconductor-insulatorsuperconductors (SIS), hot electron bolometers (HEB) and Schottky diode mixers are common detectors [8]. Recently, the UTC-PD has been demonstrated as an optically pumped mixer at frequencies up to 600 GHz [17]. However, this demonstration used an unmodulated signal with only 100 Hz of IF detection bandwidth which is not enough for communications purposes.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that an UTC-PD can be used as an OPM at frequencies up to 600 GHz [9], but these demonstrations were done within a kHz bandwidth [7,10]. In this paper, we demonstrate, for the first time, an OPM based on UTC-PD to down-convert a wireless RF signal modulated with 1 Gbaud quadrature phase shift keying (QPSK) data occupying a bandwidth of 1.35 GHz and centered at 33.5 GHz.…”
Section: Introductionmentioning
confidence: 99%